Knowledge Among Parents about Importance of Primary Dentition - Gayathri.P.S1 , Krithika. C2 , D.M.Jenisha3 , S.Kalaivani3 , V.Jenifercharuprabha3 , R.Nithyaedeinto (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: Dental caries is very common in primary dentition because of improper oral hygiene and increased intake of sucrose. The parents are the one who take care of their children and make decision for them. Often parents are responsible for the oral care of their children. The aim of this study is to evaluate the knowledge among parents about importance of primary dentition. Objectives: To evaluate the attitude and knowledge of parents towards importance of maintaining primary dentition in their children. Materials and Method: The study was conducted among parents visiting dental institution, Chennai. A total of 200 questionnaire containing 15 questions were prepared for data collection and were personally distributed to parents. A number of 100 fathers and 100 mothers were included in the study. Results: The study shows that literate parents had more knowledge about primary dentition when compared to illiterate parents. Conclusion: Knowledge about primary dentition can be increased in parents by conducting oral awareness program in schools. There is a need cultivate positive attitude among parents to raise their knowledge about dental awareness.